Phénoménologie queer: orientations, objets et autres - Ahmed, Sara (Éditions de la rue Dorion, 2022)
En se concentrant sur l’aspect « orientation » de l’« orientation sexuelle », Sara Ahmed examine ce que signifie pour les corps le fait d’être situés dans l’espace et le temps. Les corps prennent forme lorsqu’ils se déplacent dans le monde en se dirigeant vers ou loin des objets et des autres. Être « orienté » signifie se sentir chez soi, savoir où l’on se trouve, ou avoir certains objets à portée de main. Les orientations affectent ce qui est proche du corps ou ce qui peut être atteint. Selon Sara Ahmed, une phénoménologie queer révèle comment les relations sociales sont organisées dans l’espace, comment la queeresse perturbe et réordonne ces relations en ne suivant pas les chemins acceptés, et comment une politique de désorientation met à portée de main d’autres objets, ceux qui pourraient, à première vue, sembler dérangeants. Dans cet ouvrage fondateur de la réflexion sur le genre écrit en 2006, Sara Ahmed propose qu’une phénoménologie queer puisse étudier non seulement comment le concept d’orientation est informé par la phénoménologie, mais aussi l’orientation de la phénoménologie elle-même. En développant un modèle queer d’orientation, elle combine des lectures de textes phénoménologiques – de Husserl, Heidegger, Merleau-Ponty et Fanon – avec des idées tirées des études queer, de la théorie féministe, de la théorie critique des races, du marxisme et de la psychanalyse.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; féminisme décolonial; har4600; identités LGBTQIA2+; orientation; philosophie; phénoménologie; premier cycle; queer; ressource en ligne; sciences humaines; soc2014; thématiques; études critiques de la race; études féministes

The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."–The publisher.
Le chapitre 22 de Miranda Fricker et Katharine Jenkins, “Epistemic injustice, ignorance, and trans experiences” a été donné en lecture au cours FEM9000.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." – Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles